Pewarisan Silek Pauh Di Perguruan Silaturahmi Di Kelurahan Kalumbuk Kecamatan Kuranji Kota Padang - Uchi Isra Windy; Nerosti Nerosti (SENDRATASIK UNP, 2020)
This research aims to describe and discuss the inheritance of Silek Pauh at the University of Kalumbuk subdistrict, Kuranji, Padang. The method used in this study is a qualitative deskritif method. Research instruments are self-researcher and assisted by supporting instruments such as stationary cameras. The data types in this study are primary data and secondary data. Data collection techniques are conducted by way of library studies, observation, interviews, documentation.  The steps for analyzing data are data collection, describing data and making inferences. The results showed that the inheritance of Silaturahmi in this college was an open devolution system. But still rigid due to some things, among them the trainer currently has not found a candidate who is intact and able to learn the Silek Pauh.  The function of Silek Pauh in addition to martial arts and performance art, Silek Pauh is also used as a means of communication and associating among Pauh people. This seems to be seen in the practice activities Pauh Silek Many students come to Pauh Silaturahmi in this college from several villages outside the village Kalumbuk. Currently, the college has remained a sociable event between youth Kalumbuak. The process of student rektrument at the college is very easy, by coming directly and convey the goodwill to be a student in the College of Hospitality, and will be able to follow every process that is at the time of practice.